LATE MIOCENE FISH OTOLITHS FROM THE COLOMBACCI FORMATION (NORTHERN APENNINES, ITALY): IMPLICATIONS FOR THE MESSINIAN 'LAGO-MARE' EVENT - Carnevale G.; Landini W.; Caputo D. (My University, 2006)
A fish otolith assemblage from the Messinian 'Lago-mare' deposits of the Colombacci Formation cropping out in the Montecalvo in Foglia Syncline, Marche, central Italy, is described. The assemblage displays a low diversity and consists of seven taxa belonging to three families: the Gobiidae, Myctophidae and Sciaenidae. Sciaenid otoliths are the most abundant elements representing 88% of the entire assemblage. The palaeoecological analysis reveals a coastal shallow marine environment strongly influenced by continental outflow. The low diversity and high abundance of the euryecious sciaenids are indicative of a very simplified food web, which probably represented an ecological response to the fluctuating environmental parameters and available food resources. The fish remains documented here provide an unambiguous evidence that normal marine conditions were present in the Mediterranean, at least in the upper part of the 'Lago-mare' event, and unquestionably demonstrate that the marine refilling preceded the Mio-Pliocene boundary. These findings clearly demonstrate that fishes, because of their mobility and migratory behaviour, represent a useful tool for the large-scale interpretation of the environmental conditions of the Messinian Mediterranean water body. The necessity of a new scenario of palaeoenvironmental evolution for the post-evaporitic Messinian of the Mediterranean is also discussed. Copyright © 2006 John Wiley & Sons, Ltd.
Keywords: 'LAGO-MARE'; FISH OTOLITHS; MEDITERRANEAN; MESSINIAN; NORTHERN APENNINES; PALAEOENVIRONMENT; Cenozoic::Neogene::Miocene::Messinian; Кайнозой::Неоген::Миоцен::Мессинский